2019
DOI: 10.48550/arxiv.1907.08172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The structure and free resolutions of the symbolic powers of star configurations of hypersurfaces

Abstract: Star configurations of hypersurfaces are schemes in P n widely generalizing star configurations of points. Their rich structure allows them to be studied using tools from algebraic geometry, combinatorics, commutative algebra and representation theory. In particular, there has been much interest in understanding how "fattening" these schemes affects the algebraic properties of these configurations or, in other words, understanding the symbolic powers I (m) of their defining ideals I.In the present paper (1) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…For other results on this topic we can also see [27,47]. Another tool useful to measure the non-containment among symbolic and ordinary powers of ideals is the notion of resurgence ρ(I) of an ideal I, introduced in [9] that gives some notion of how small the ratio m/r can be and still be sure to have I (m) ⊆ I r .…”
Section: B Harbourne Conjectured In [4]mentioning
confidence: 99%
“…For other results on this topic we can also see [27,47]. Another tool useful to measure the non-containment among symbolic and ordinary powers of ideals is the notion of resurgence ρ(I) of an ideal I, introduced in [9] that gives some notion of how small the ratio m/r can be and still be sure to have I (m) ⊆ I r .…”
Section: B Harbourne Conjectured In [4]mentioning
confidence: 99%
“…It has been of great interest to study various algebraic, geometric and combinatorial properties of star configurations; see for instance [3], [12], [13], [18] and the references therein. The object we are mostly interested here is the defining ideal…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, these symbolic power ideals will have linear-like resolutions. This idea was later made more precise by Mantero in [18] by the notion of Koszul stranded Betti table; see Definition 1.2 below. Actually he showed that these ideals have complete intersection quotients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly after this paper was posted on arXiv, another preprint appeared by Paolo Mantero [Man19] which also computes the graded Betti numbers of symbolic powers of star configurations. The results in Mantero's preprint were obtained independently from ours, and utilize new and interesting techniques.…”
Section: Introductionmentioning
confidence: 99%